From prosperity into the crisis and back. On the role of economic theories in the long cycle - Schulmeister, Stephan (Vienna, 2018)
"This essay reconsiders the interaction between the development of economic theories and economic reality since the 1920ies. I begin with the systemic cause of the financial crisis, the coincidence of three "bear markets" (stocks, real estate, commodities) which followed three parallel "bull markets". I then sketch the macroeconomic effects of the "manic-depressive" fluctuations of asset prices and show how they paved the road into the present crisis. As next step, I explain how "bulls" and "bears" are brought about. Then I sketch how the treatment of financial markets in economic theory and policy has shaped the long cycle from the financial boom of the 1920ies, the Great Depression, the post-war prosperity under "realcapitalistic" framework conditions to the "finance-capitalistic" regime since the 1970ies. The paper concludes with proposals how Europe could find roads to new prosperity. After the upcoming financial crisis there will be a window of opportunity to implement these proposals."